Nanomaterial‐based biosensors for sensing key foodborne pathogens: Advances from recent decades. Issue 4 (7th June 2020) - Zhang, Ruyuan; Belwal, Tarun; Li, Li; Lin, Xingyu; Xu, Yanqun; Luo, Zisheng
Abstract: Foodborne pathogen contamination has become a severe threat to human health. Traditional methods for foodborne pathogen detection have several disadvantages, including long detection time, low sensitivity, and low selectivity. The emergence of multiple excellent nanomaterials enables the construction of novel biosensors for foodborne pathogen detection. Based on the outstanding properties of nanomaterials, the novel biosensors possess the advantages of sensitivity, specificity, rapidity, accuracy, and simplicity. The present review comprehensively summarizes the advanced biosensors, including electrochemical, colorimetric, fluorescent, and surface enhanced Raman scattering biosensors for sensing key foodborne pathogens in recent decades. Furthermore, several issues are identified for further exploration, and possible directions for the development of biosensors are discussed.